Functional analysis of pollen tube growth dynamics in banana (Musa spp.) - Severyns, A.; Claessen, H.; Swennen, R.; Janssens, S.B.; Simba, R.; Brown, A.; De Storme, N. (Elsevier, 2025)
Bananas and plantains (Musa spp.) are major tropical fruit crops, though the development of new cultivars is hindered by the high degree of female sterility in existing varieties. One major issue is the pollination step, and particularly the lack of optimized, research-based pollination practices. This study aimed to better understand pollen tube growth dynamics in Musa to inform and improve pollination strategies in breeding programs. Pollen tube growth dynamics were assessed in several controlled crosses using both wild diploid and cultivated diploid/triploid varieties. Pre-anthesis pollination as well as the timing of pollination during the day (morning vs. evening), were also tested to evaluate their influence on pollen tube growth. We found that in wild diploids, pollen tubes reached the ovary within 48 h after pollination, while in cultivars pollen tubes progressed more slowly, reaching the ovary only after 72 h and in reduced numbers. Pollination of pistils before anthesis consistently resulted in less pollen adhesion and fewer and slower-growing pollen tubes. Similarly, using immature pollen during pollination in the evening led to less pollen tube growth. However, when mature pollen was used on pistils at anthesis, no difference was observed between morning and evening pollination. These results identified problems with pollen retention and pollen tube growth as key hybridization barriers in Musa cultivars. Despite these limitations, some pollen tubes still reached the ovary, suggesting room for improvement. We recommend using only post-anthesis flowers in breeding crosses to enhance pollination efficiency and fertilization success.